Actividad biocida de las sustancias bioactivas de Azadirachta indica A. Juss. y Ocimum basilicum L., sobre adultos de Aedes aegypti, Trujillo-Perú-2018. - Huaman Medrano, Edwin Abel (2019)
ABSTRACT Aedes aegypti is a vector of importance in public health in Peru, for transmitting viruses such as dengue, chikungunya and zika. Synthetic insecticides are used to control this vector, but over time, the vector generates resistance, which is why new control alternatives are being sought, such as the use of bioactive substances from medicinal plants. The present work evaluated the biocidal activity of the bioactive substances of Azadirachta indica A. Juss. and Ocimum basilicum L., on adults of Aedes aegypti. Collection, taxonomic identification, study of the quality of the vegetable drug, obtaining fluid extracts, obtaining essential oils, phytochemical Screnning of the plant species Azadirachta indica A. Juss. was carried out. “neem” and Ocimum basilicum L. “basil” and finally the bioassay of the biocidal activity against adults of Ae. aegypti from Rio Seco (Trujillo), Ferreñafe (Chiclayo) and Sullana (Piura). He present work reported the following results: the aqueous extract (12.32 mg / mL), hydroalcoholic of 70 ° GL (10.2 mg / mL), hexane (5.1 mg / mL) of the “neem” had effect on adults of Ae. aegypti strain Rio Seco and Ferreñafe, for the Sullana strain additionally the ethyl acetate extract (6.3 mg / mL); the fixed oil (207 mg / mL) did not show any effect. For “basil”, the aqueous extract (31.3 mg / mL), hydroalcoholic of 70 ° GL (21.7 mg / mL), hexane (32.6 mg / mL), essential oil (200 μL / mL) had an effect on adults of Ae. aegypti strain Rio Seco and Ferreñafe, while for the Sullana strain the hydroalcoholic extract of 70 ° GL (21.7 mg / mL), did not show any effect. Some fluid extracts and essential oils have a biocidal effect on adults of Ae. aegypti strain Rio Seco, Ferreñafe and Sullana.